TINJAUAN UNDANG - UNDANG NO.18 TAHUN 2011 TENTANG KOMISI YUDISIAL GUNA TERWUJUD PERADILAN YANG BERSIH DI PENGADILAN NEGERI SEMARANG - Sefrin Ibnu (Fakultas Hukum Universitas Stikubank, 2021)
The enforcement of justice as an important element of human rights, should actually be built and realized in any legal state system. In addition to presenting a quality judicial system and personnel, it also needs to be supported by a mechanism for recruiting and fostering judges and other law enforcers who are honest and with integrity. judicial commission which is officially mandated by the constitution and Law no. 18 of 2011 to realize the authority of the judiciary so that it will be trusted again by the community.2The Judicial Commission, which was born because of the reform, is aimed at creating a clean, independent, independent, transparent judiciary and upholding justice for all levels of society. Moreover, the constitution clearly states that the main authority of the Judicial Commission is to maintain and uphold the honor, dignity, and behavior of judges.The implementation of Law No. 18 of 2011 concerning the Judicial Commission in the realization of a clean judiciary in the Semarang District Court is carried out by establishing a liaison for the judicial commission in the regions, in this way the judicial commission carries out its duties and functions as a liaison for the creation of a clean court system in the Semarang District Court. This is in accordance with Article 3 paragraph (2) of Law Number 18 of 2011 concerning the Judicial Commission which reads